PENGELOLAAN SDM UMKM DI ERA DIGITAL PADA PULAU HARAPAN, KEPULAUAN SERIBU - Estiana, Ria; Nurdin; Damiyana, Damdam; Pramulanto, Himawan; Akhmad, Jaenudin (JURNAL ABDIMAS PLJ, 2024)
Effective and adaptive management of Human Resources (HR) to the development of digital technology is the key to the success of Micro, Small, and Medium Enterprises (MSMEs) in the modern era. Harapan Island, one of the islands in the Thousand Islands, DKI Jakarta, has great economic potential, especially from the MSME sector. However, limitations in human resource management and the use of digital technology are the main challenges for the growth and sustainability of MSMEs in this region. This community service activity aims to increase the capacity of MSME human resource management on Harapan Island through the application of digital technology. This program includes training and assistance in the use of digital tools for human resource management, the development of basic digital skills for MSME actors, and increasing digital literacy among MSME workers. The methodology used includes workshops, intensive training sessions, and direct mentoring in the field.  It is hoped that through this program, MSMEs on Harapan Island can optimize their human resource management, improve operational efficiency, and expand market reach through digital technology. In addition, this program also aims to build awareness and better understanding of the importance of digitalization in business management. Thus, MSMEs on Harapan Island can develop better and contribute more significantly to the local economy and the welfare of the local community.